Tinnitus Treatment Using Noninvasive and Minimally Invasive Electric Stimulation: Experimental Design and Feasibility - Zeng, Fan-Gang (Trends Hear, 2019)
Noninvasive transcranial or minimally invasive transtympanic electric stimulation may offer a desirable treatment option for tinnitus because it can activate the deafferented auditory nerve fibers while posing little to no risk to hearing. Here, we built a flexible research interface to generate and control accurately charge-balanced current stimulation as well as a head-mounted instrument capable of holding a transtympanic electrode steady for hours. We then investigated the short-term effect of a limited set of electric stimulation parameters on tinnitus in 10 adults with chronic tinnitus. The preliminary results showed that 63% of conditions of electric stimulation produced some degree of tinnitus reduction, with total disappearance of tinnitus in six subjects in response to at least one condition. The present study also found significant side effects such as visual, tactile, and even pain sensations during electric stimulation. In addition to masking and residual inhibition, neuroplasticity is likely involved in the observed tinnitus reduction. To translate the present electric stimulation into a safe and effective tinnitus treatment option, we need to optimize stimulation parameters that activate the deafferented auditory nerve fibers and reliably suppress tinnitus, with minimal side effects and tolerable sensations. Noninvasive or minimally invasive electric stimulation can be integrated with sound therapy, invasive cochlear implants, or other forms of coordinated stimulation to provide a systematic strategy for tinnitus treatment or even a cure.